Complete overdentures retained by mini implants: A systematic review - Araujo Lemos, Cleidiel Aparecido [UNESP] (2017)
Objective: The purpose of this systematic review was to evaluate the use of mini implants to retain complete overdentures in terms of survival rates of mini implants, marginal bone loss, satisfaction, and quality of life. Data: This report followed the PRISMA Statement and PICO question. This review has been registered at PROSPERO under the number CRD42016036141. Source: Two independent reviewers performed a comprehensive search of studies published until September 2016 and listed in the PubMed/MEDLINE, Embase, and The Cochrane Library databases. The focused question was: is the use of mini implants feasible for prosthodontic rehabilitation with complete overdentures? Results: The 24 studies selected for review evaluated 1273 patients whose mean age was 65.93 years; these patients had received 2494 mini implants and 386 standard implants for retaining overdenture prosthesis. The mean follow-up time was 2.48 years (range: 1-7 years). There was a higher survival rate of mini implants (92.32%). More frequent failures for maxillary (31.71%) compared with mandibular arches (4.89%). The majority of studies revealed marginal bone loss values similar to those of standard implants (< 1.5 mm). All studies verified an increase in satisfaction and quality of life after rehabilitation treatment with mini dental implants. Conclusion: The present systematic review indicates that the use of mini implants for retaining overdenture prosthesis is considered an alternative treatment when standard treatment is not possible, since it presents high survival rates, acceptable marginal bone loss, and improvements in variables related to satisfaction and quality of life. Clinical significance: Based on the results of this study, the use of a minimum 4 and 6 mini implants can be considered a satisfactory treatment option for rehabilitation of the mandibular and maxillary arches respectively with a complete overdenture. (C) 2016 Published by Elsevier Ltd.